The Molecular Fingerprint of Dorsal Root and Trigeminal Ganglion Neurons - Lopes, Douglas M.; Denk, Franziska; McMahon, Stephen B. (Frontiers in Molecular Neuroscience, 2017)
The dorsal root (DRG) and trigeminal ganglia (TG) are clusters of cell bodies of highly specialised sensory neurons which are responsible for relaying information about our environment to the central nervous system. Despite previous efforts to characterise sensory neurons at the molecular level, it is still unknown whether those present in DRG and TG have distinct expression profiles and therefore a unique molecular fingerprint. To address this question, we isolated lumbar DRG and TG neurons using fluorescence-activated cell sorting (FACS) from Avil-GFP transgenic mice and performed RNA sequencing. Our transcriptome analyses showed that, despite being overwhelmingly similar, a number of genes are differentially expressed in DRG and TG neurons. Importantly, we identified twenty-four genes which were uniquely expressed in either ganglia, including an arginine vasopressin receptor and several homeobox genes, giving each population a distinct molecular fingerprint. We compared our findings with published studies to reveal that many genes previously reported to be present in neurons are in fact likely to be originated from other cell types in the ganglia. Additionally, our neuron-specific results aligned well with a dataset examining whole human TG and DRG. We propose that the data can both improve our understanding of primary afferent biology and help contribute to the development of drug treatments and gene therapies which seek targets with unique or restricted expression patterns.